Becoming a resident in Germany: an experience-based practical guideline - Bogdanyova, Sandra; Lermann, Johannes; Mendes, Miguel De Sousa; Schott, Sarah (Archives of Gynecology and Obstetrics, 2015)
Many young doctors in Europe and beyond are considering different career alternatives. Germany is one of the most sought after countries for medical specialization. Since there is no centralized structured application process, course, or nationwide rotating program, it may seem a little bit easier to find job opportunities in Germany than in other European countries. However, the process of changing country of residence, looking for and finding new employment, and obtaining all the required paperwork is far from easy. It is therefore essential to gather as much information about the application and its process when considering a career move in order to be well prepared about what may come before and after applying for a resident position.The essential information about the application possibilities and process were reviewed and summarized.This article provides a practical guide on how to proceed when considering job opportunities as a resident in Germany, the application process, and what to expect once a job has been found.
EVALuna2:17628